Implicit Costs and Investment Behavior in Thailand’s Large Plot Scheme for Rice Farming: A Case Study of Maklua Mai Subdistrict, Sung Noen District, Nakhon Ratchasima Province - Manorat, Tula Khomkit (Ratchaphruek Journal, 2026)
Implicit costs, which are not expressed as cash outflows, influence farm production planning and investment decisions and are frequently overlooked in production accounting. This study aims to 1) examine the structure, components, and value of implicit costs in rice farming under Thailand’s Large Plot Scheme across different production systems; and 2) analyze differences in production planning behavior and tendencies toward economic sustainability according to levels of implicit costs and production systems. A mixed-methods approach was employed, comprising quantitative data from 96 rice farmers and in-depth interviews, grounded in microeconomic production theory and agricultural household investment behavior. The findings show that implicit costs accounted for 37–57 percent of total production costs. Farmers using chemical fertilizers had the lowest share of implicit costs, while those outside irrigation areas faced the highest. Production and investment behavior differed by cost level: farmers with low implicit costs tended to make bolder investment decisions and relied less on internal resources, whereas those with high implicit costs adopted more conservative planning. Farmers with mid-level implicit costs demonstrated flexible production planning and greater use of information to support decision-making. Policy recommendations include promoting farm accounting systems that record implicit costs, strengthening group management mechanisms, and developing state measures to reflect the true economic cost structure of farmers.